2018
DOI: 10.4236/ojped.2018.84032
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Health Professionals on Essential Newborn Care in Bamako, Mali

Abstract: Despite existing policies on training health professionnels in essential newborn care (ENC), neonatal mortality still remains high in Mali. Our work aimed to assess the level of knowledge of health staff about ENC. Material and methods: From March 20 th to April 20 th , 2016, we interviewed newborn care providers at the six reference health centers and the Gabriel Touré University Hospital Center in Bamako. Results: In total, we interviewed 407 newborn care providers with a sex ratio of 0.52. Interviewees had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
4
4
0
Order By: Relevance
“…This result was agreed with a study who revealed that professional experience in midwifery for the study sample was more than five years (12) . The majority (67.5%) of study sample were received a training course in newborn care.…”
Section: Resultssupporting
confidence: 93%
“…This result was agreed with a study who revealed that professional experience in midwifery for the study sample was more than five years (12) . The majority (67.5%) of study sample were received a training course in newborn care.…”
Section: Resultssupporting
confidence: 93%
“…And mean (±SD) experience in delivery room was (6.53 5.94), the majority (52.5%) were ranged between (1-5 ) years. This result was agreed with Traore (2018) who revealed that the study sample have more than five years of professional experience in midwifery (12) . Negussie et al, (2018) concluded that two third of the study participants had less than six years' experience of delivery care service (13) .…”
Section: Resultssupporting
confidence: 92%
“…In this study the overall knowledge score of essential new born was 61.7% at 95% CI (56.4, 69.8)] which is in line with the Study conducted in Wolaita zone southern Ethiopia in which knowledge score of ENC was 57.9 % [21] and in Bahirdar 56% [22]. But this nding was higher than the study conducted in Bamako in Mali 54% [23] and in Masindi Uganda was 46.5% [24] .However our nding is less than the study conducted in India was 76% [25] and in Tigray was 74.6% [26].The discrepancy could be due to the difference in in-service training, difference of educational level of study participants and study setting.…”
Section: Discussionsupporting
confidence: 87%